2019
DOI: 10.7287/peerj.preprints.27926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melody matters: An acoustic study of domestic cat meows in six contexts and four mental states

Abstract: 14This study investigates domestic cat meows in different contexts and mental states. Measures of 15 fundamental frequency (f0) and duration as well as f0 contours of 780 meows from 40 cats were 16 analysed. We found significant effects of recording context and of mental state on f0 and 17 duration. Moreover, positive (e.g. affiliative) contexts and mental states tended to have rising f0 18 contours while meows produced in negative (e.g. stressed) contexts and mental states had 19 predominantly falling f0 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We can suppose that while the separation/confinement test was probably a negative experience for all the cats, the human approach test was a positive experience for at least some individuals. A more detailed acoustic analysis of the meows may help disentangle the emotional valence and motivation (e.g., stress, attention-seeking, greeting) underlying them in these tests, since meows emitted during distress have a distinct pattern (low mean fundamental frequency, longer duration; Schötz et al [ 85 ]). Additionally, the cats for which the human approach test was a positive experience may have emitted other vocalizations (e.g., purrs, which Fermo et al [ 86 ] found are exclusively associated with positive experiences).…”
Section: Discussionmentioning
confidence: 99%
“…We can suppose that while the separation/confinement test was probably a negative experience for all the cats, the human approach test was a positive experience for at least some individuals. A more detailed acoustic analysis of the meows may help disentangle the emotional valence and motivation (e.g., stress, attention-seeking, greeting) underlying them in these tests, since meows emitted during distress have a distinct pattern (low mean fundamental frequency, longer duration; Schötz et al [ 85 ]). Additionally, the cats for which the human approach test was a positive experience may have emitted other vocalizations (e.g., purrs, which Fermo et al [ 86 ] found are exclusively associated with positive experiences).…”
Section: Discussionmentioning
confidence: 99%
“…The mew, as the other vocalization is highly modulated by the context in which vocalizations are recorded. A recent study of Schötz et al [26] shows that mew produced in positive context differ in their pitch (higher), duration (shorter), and melody (rising) to mew produced in negative context.…”
Section: Mew (Miaow)mentioning
confidence: 99%
“…Also, the intentions of the emitter are expressed in the vocalization. The modification of the acoustic parameters (duration, source, tonality, or fundamental frequency [Fo]) would allow a change of the message that represents the cat's internal conditions during an agonistic encounter or isolation [7,26]. The agonistic sounds are described as aggressive or defensive sounds used to warn, shock, or startle an intruder or attacker [9].…”
Section: Vocalization Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another cat-inspired sidenote, I would like to point to the real cat language of the Meowsic research project. The Meowsic project looks at melody in human-cat communication and wants to provide an understanding of prosodic features in human speech and cat vocalisations (Schötz, Eklund & van de Wejer, 2016).…”
Section: Lolspeak – a Cat Related Internet Varietymentioning
confidence: 99%